Agricultural growth in Ethiopia (2004-2014): Evidence and drivers - Bachewe, Fantu Nisrane; Berhane, Guush; Minten, Bart; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2015)
Ethiopia’s agricultural sector has recorded remarkable rapid growth in the last decade. This paper documents aspects of this growth process. Over the last decade, there have been significant increases - more than a doubling - in the use of modern inputs, such as chemical fertilizers and improved seeds, explaining part of that growth. However, there was also significant land expansion, increased labor use, and Total Factor Productivity (TFP) growth, estimated at 2.3 percent per year. The expansion in modern input use appears to have been driven by high government expenditures on the agricultural sector, including agricultural extension, but also by an improved road network, higher rural education levels, and favorable international and local price incentives.